Certain aspects of the modernization process in Japan - Akyn, B. K. (Journal of Oriental Studies, 2016)
This paper is devoted to study some features of the modernization process in Japan, including analize the East Asian model in the context of the general theory of modernization. The author also said that the Japanese model of modernization in the mid-19th century to the present has become the object of comparative analysis. In addition, they were researched the theoretical issues of modernization.